Preclinical Evaluation of Poly(HEMA-co-acrylamide) Hydrogels Encapsulating Glucose Oxidase and Palladium Benzoporphyrin as Fully Implantable Glucose Sensors - Unruh, Rachel M. (J Diabetes Sci Technol, 2015)
BACKGROUND: Continuous glucose monitors (CGMs) require percutaneous wire probes to monitor glucose. Sensors based on luminescent hydrogels are being explored as fully implantable alternatives to traditional CGMs. Our previous work investigated hydrogel matrices functionalized with enzymes and oxygen-quenched phosphors, demonstrating sensitivity to glucose, range of response, and biofouling strongly depend on the matrix material. Here, we further investigate the effect of matrix composition on overall performance in vitro and in vivo. METHODS: Sensors based on three hydrogels, a poly(2-hydroxyethyl methacrylate) (pHEMA) homopolymer and 2 poly(2-hydroxyethyl methacrylate-co-acrylamide) (pHEMA-co-AAm) copolymers, were compared. These were used to entrap glucose oxidase (GOx), catalase, and an oxygen-sensitive benzoporphyrin phosphor. All sensor formulations were evaluated for glucose response and stability at physiological temperatures. Selected sensors were then evaluated as implanted sensors in a porcine model challenged with glucose and insulin. The animal protocol used in this study was approved by an IACUC committee at Texas A&M University. RESULTS: PHEMA-co-AAm copolymer hydrogels (75:25 HEMA:AAm) yielded the most even GOx and dye dispersion throughout the hydrogel matrix and best preserved GOx apparent activity. In response to in vitro glucose challenges, this formulation exhibited a dynamic range of 12-167 mg/dL, a sensitivity of 1.44 ± 0.46 µs/(mg/dL), and tracked closely with reference capillary blood glucose values in vivo. CONCLUSIONS: The hydrogel-based sensors exhibited excellent sensitivity and sufficiently rapid response to the glucose levels achieved in vivo, proving feasibility of these materials for use in real-time glucose tracking. Extending the dynamic range and assessing long-term effects in vivo are ongoing efforts.